Oliveria decumbens and Pistacia atlantica Gum's Essential Oils: Assessment of Antimicrobial and Chemical Properties During Thermal Process - S.J. Hosseini; M. Shahidi-Noghabi; H. Zamani; Gh. Zohuri; Mahboubeh Sarabi (مجله پژوهش‌های علوم و صنایع غذایی ایران, 2023)
The essential oils usually have a good effect against undesirable microorganisms; therefore, they can be utilized as natural antimicrobial agents in food or their packaging. In this research, the antimicrobial attributes of two essential oils (Oliveria decumbens and Pistacia atlantica gum), have been investigated before and after thermal process (200°C - 10 minutes) against bacterial and mold spoilage in bread. Also, the compounds of essential oils were detected by gas chromatography-mass spectrometry. The main compounds of the essential oil of O. decumbens were carvacrol, thymol, and elemicin before and after thermal treatment. In the case of P. atlantica gum, only one prominent peak was observed in the chromatogram, which was related to the α-pinene. For both essential oils, the MIC and MFC against Aspergillus niger were 4000 and 8000 μL/ml, respectively. In comparison, the antimicrobial effect of both essential oils against Bacillus subtilis was higher than the mold. The amount of MIC and MBC were 125 and 250 μL/ml for Oliveria decumbens and 62.5 and 125 μL/ml for Pistacia atlantica gum, respectively. The results showed that these two essential oils have a promising effect against the main microorganisms of bread spoilage. The thermal process did not significantly affect the antimicrobial activity of Pistacia atlantica gum essential oil against A. niger but significantly decreased the antimicrobial activity against B. subtilis, while in the case of antimicrobial activity of Oliveria decumbens essential oil, the results were the opposite. Considering the fact that the most spoilage agents of the bread are molds so the use of Pistacia atlantica gum essential oil is recommended as natural preservatives in products that tolerate high heat treatment, such as bread and bakery products.